TASHKENT PEDIATRIC INSTITUTE OF ACADEMIC LYCEUM (Modern education and development, 2025)
Teaching English can and should provide the achievement of practical, educational and developing aims. Besides, the practical purpose the leading. The other purposes are reached in the course of mastering English in the conditions of pupils' active informative of power of apprehension and activity. Pedagogy, guiding and synthesizing these aspects, defines vision of a problem from its specific point of view.